The Pain Intensity/Quality and Pain Site Association with Muscle Activity and Muscle Activity Distribution in Patients with Chronic Low Back Pain: Using a Generalized Linear Mixed Model Analysis - Hayato Shigetoh; Yuki Nishi; Michihiro Osumi; Shu Morioka (Pain Research and Management)
Background. Pain can alter muscle activity, although it is not clear how pain intensity and site location affect muscle activity. This study aimed to reveal the complex associations among the pain site, pain intensity/quality, muscle activity, and muscle activity distribution. Methods. Electromyographic signals were recorded from above a bilateral lumbar erector spinae muscle with a four-channel electrode in 23 patients with chronic low back pain while they performed a lumbar bending and returning task. We calculated the average value of muscle activity during the extension phase (agonist activity) and the centroid of muscle activity, as well as the distance between the centroid of muscle activity and pain site. We also assessed the pain site and pain intensity/quality by the interview and questionnaire method. A generalized linear mixed model analysis was performed to determine the relationships among pain intensity/quality, pain site, and muscle activity. Results. The results showed that muscle activity during the extension phase was significantly negatively associated with neuropathic pain and “pain caused by light touch.” In addition, the distance between the centroid of muscle activity and pain site during the extension phase was significantly positively associated with intermittent pain, “throbbing pain,” “splitting pain,” “punishing-cruel,” and “pain caused by light touch.” Conclusions. Our findings suggest the existence of a motor adaptation that suppresses muscle activity near the painful area as the pain intensity increases. Furthermore, the present study indicates that the presence or absence of this motor adaptation depended on the pain quality.